Software development outsourcing risk factors and severity level: An empirical investigation - Abd Wahab, Alawiyah; Yahaya, Jamaiah; Ahmad, Faudziah; Farina Zakaria, Siti; Razak Hamdan, Abdul; Deraman, Aziz (International Journal of Engineering and Technology, 2018)
Software development outsourcing has become an important business strategy both in the public and private sectors not only in Malaysia but also worldwide. This is because it has the potential of lowering the operation cost, improving the quality of service and gaining access to advanced technological expertise. Although outsourcing can be very beneficial, it entails risks that could cause significant loss if organizations fail to identify and manage them. This study aims to identify and assess the severity level of risk factors involved in an outsourced software development project from the practitionersâ€™ perspective. Therefore, a survey has been conducted with 132 practitioners from the public sectors in the selected states within the northern Peninsular Malaysia. The survey included the risk factors identified in a thorough literature review study. The total mean value indicated of six main risk factors, four main risk factors are very highly critical.Â